Magnetic core and magnetic component
Patent Information
- Application Number
- CN202310117279.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-21
- Filing Date
- 2023-02-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-02-15
AI Technical Summary
[0004]但是,若提高磁性粉末的填充率,则磁性颗粒彼此的接触点增加,因此磁心的耐电压有降低的倾向
[0027]本公开的磁性体芯能够应用于电感器、变压器、扼流线圈等各种磁性部件。
Smart Images

Figure CN116631719B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to magnetic cores and magnetic components. Background Technology
[0002] Magnetic components such as inductors, transformers, and choke coils are widely used in the power supply circuits of various electronic devices. In recent years, in the face of a low-carbon society, the reduction of energy loss and the improvement of power supply efficiency in power supply circuits have received attention, requiring higher efficiency and energy saving of magnetic components.
[0003] To meet the aforementioned requirements for magnetic components, it is essential to increase the relative permeability of the magnetic core contained within the magnetic component. Furthermore, to increase the relative permeability of the core, it is necessary to increase the filling rate of the magnetic powder contained within the core. Therefore, in the field related to magnetic components, various attempts have been made to increase the filling rate of the magnetic powder in the core. For example, Patent Document 1 discloses that by adjusting the distance between the edges of large particles and the distance between the centers of gravity of coarse particles to a predetermined range, the filling density of the magnetic powder can be increased.
[0004] However, increasing the filling rate of the magnetic powder increases the contact points between the magnetic particles, which tends to reduce the withstand voltage of the magnetic core. Furthermore, the increased contact points can cause localized magnetic saturation, leading to a deterioration of the DC superposition characteristics. In other words, the filling rate (relative permeability) is in a trade-off with both withstand voltage and DC superposition characteristics; a high filling rate (relative permeability) makes it difficult to simultaneously improve both withstand voltage and DC superposition characteristics.
[0005] [Existing technical documents]
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-176167 Summary of the Invention
[0007] [The problem the invention aims to solve]
[0008] This disclosure was made in view of the above-mentioned circumstances, and its purpose is to provide a magnetic core having both high voltage resistance and excellent DC superposition characteristics, and a magnetic component having the magnetic core.
[0009] [Methods used to solve problems]
[0010] To achieve the above objectives, the magnetic core disclosed herein comprises metallic magnetic powder and resin.
[0011] Let A1 be the area of the metallic magnetic powder on the cross-section of the magnetic core, and let A2 be the total area of the metallic magnetic powder and the resin. The content of the metallic magnetic powder shall satisfy 60% ≤ (A1 / A2) ≤ 90%.
[0012] The aforementioned metallic magnetic powder contains small particles with a black hole diameter of less than 1 μm and large particles with a diameter of more than 5 μm but less than 40 μm on the cross-section of the aforementioned magnetic core.
[0013] Let the radius of each of the above small particles be r. N ,
[0014] Let the average black oode diameter of the above small particles be dav.
[0015] On the cross-section of the aforementioned magnetic core, from the center of gravity of each of the aforementioned small particles to a radius of 3r N The area within the circumference is considered as the vicinity of each small particle.
[0016] In the aforementioned vicinity of each small particle, the distance between the edge of the small particle located at the center and the edge of the small particle furthest from the center is defined as L1.
[0017] Let the average value of L1 be L1av.
[0018] The ratio of L1av to dav satisfies 5 ≤ ((L1av / dav) × 100) ≤ 70.
[0019] On the cross-section of the aforementioned magnetic core, let L2 be the distance between the edges of any large particle and any small particle adjacent to the large particle. Let L2 be the average value of L2, and let σ be the standard deviation of L2.
[0020] L2av is above 0.02μm and below 0.13μm.
[0021] σ is below 0.25μm.
[0022] By giving the magnetic core the above characteristics, it is possible to maintain a high relative permeability and improve voltage resistance and DC superposition characteristics compared with the present.
[0023] Preferably, the average roundness of the large particles on the cross-section of the magnetic core is 0.8 or higher.
[0024] On the cross-section of the aforementioned magnetic core, let the area occupied by the small particles be S1.
[0025] On the cross-section of the aforementioned magnetic core, the area occupied by the large particles is S2.
[0026] Preferably, the ratio of S1 to S2 satisfies 0.2≤(S1 / S2)≤0.5.
[0027] The magnetic core disclosed herein can be applied to various magnetic components such as inductors, transformers, and choke coils. Attached Figure Description
[0028] Figure 1 This is a schematic cross-sectional view showing a magnetic core according to one embodiment of the present disclosure.
[0029] Figure 2 It means Figure 1 A schematic diagram of an example of the particle size distribution of the metallic magnetic powder contained in a magnetic core.
[0030] Figure 3A This is a schematic diagram illustrating the cross-sectional analysis method for a magnetic core.
[0031] Figure 3B This is a schematic diagram illustrating the cross-sectional analysis method for a magnetic core.
[0032] Figure 3C This is a schematic diagram illustrating the cross-sectional analysis method for a magnetic core.
[0033] Figure 4 This is an example of a SEM image showing a cross-section of the magnetic core involved in this disclosure.
[0034] Figure 5 This is a cross-sectional view showing an example of the magnetic component involved in this disclosure.
[0035] Symbol Explanation
[0036] 2…Magnetic core
[0037] 10…Metallic magnetic powder
[0038] 10a…micro powder
[0039] 10b…Main Fan
[0040] 11… small particles
[0041] 12… large particles
[0042] 20…resin
[0043] 100…Magnetic components
[0044] 5…coil
[0045] 5a…end
[0046] 5b…end
[0047] 6, 8... External electrodes Detailed Implementation
[0048] The present disclosure will now be described in detail based on the embodiments shown in the accompanying drawings.
[0049] The magnetic core 2 involved in this embodiment only needs to be formed into a prescribed shape, and its external dimensions and shape are not particularly limited. For example Figure 1 As shown in the schematic cross-sectional view, the magnetic core 2 contains at least metallic magnetic powder 10 and resin 20. The constituent particles of the metallic magnetic powder 10 are bonded together by the resin 20, thereby giving the magnetic core 2 a predetermined shape.
[0050] Let A1 be the area occupied by the metallic magnetic powder 10 in the cross-section of the magnetic core 2, and let A2 be the total area of the metallic magnetic powder 10 and the resin 20. A2 is equivalent to Figure 1 The area of any cross-section of the magnetic core 2 shown, and the filling rate of the metallic magnetic powder 10 in the magnetic core 2, can be expressed as A1 / A2. A1 / A2 in the magnetic core 2 is 60% or more and 90% or less, preferably 75% or more and 90% or less. It should be noted that A1 / A2 can be calculated by analyzing the cross-section of the magnetic core 2 using an electron microscope or the like. For example, an arbitrary cross-section of the magnetic core 2 is divided into multiple consecutive fields of view for observation, and the area of the metallic magnetic powder contained in each field of view is measured. In this case, it is preferable to set the area of each field of view to be equivalent to an area of 100 μm × 100 μm, and the number of observed fields of view to be at least 100. That is, it is preferable to set the total area of the fields of view when measuring A1 to be at least 1,000,000 μm. 2 Calculate A1 / A2.
[0051] The metallic magnetic powder 10 is composed of soft magnetic metal particles, including: small particles 11 with a Heywood diameter of less than 1 μm, and large particles 12 with a Heywood diameter of 5 μm or more but less than 40 μm. In addition to the small particles 11 and large particles 12, the metallic magnetic powder 10 may also contain medium particles with a Heywood diameter greater than 1 μm but less than 5 μm, and coarse particles with a Heywood diameter of 40 μm or more. It should be noted that in this embodiment, the "Heywood diameter" refers to the equivalent circle diameter of each particle observed in the cross-section of the magnetic core 2. Specifically, the area of each soft magnetic metal particle in the cross-section of the magnetic core 2 is denoted as S, and the Heywood diameter of each soft magnetic metal particle is expressed as (4S / π). 1 / 2 express.
[0052] Furthermore, the metallic magnetic powder 10 preferably comprises two or more particle groups with different average particle sizes. The particle group composition of the metallic magnetic powder 10 can be determined by obtaining the particle size distribution of the metallic magnetic powder 10 based on the Hausude diameter of each soft magnetic metal particle observed in the cross-section of the magnetic core 2. For example, Figure 2 The chart shown is an example of the particle size distribution of metallic magnetic powder 10. Figure 2 The vertical axis represents the frequency (%) based on a number basis. Figure 2The horizontal axis is the logarithmic axis representing the particle size (μm) converted from the Hawde diameter.
[0053] In the case where the metallic magnetic powder 10 consists of two particle groups, such as Figure 2 As shown, the particle size distribution of the metallic magnetic powder 10 has two peaks. In this embodiment, the peak on the side with smaller particle size is referred to as the first peak (Peak1), and the particle group possessing this first peak is referred to as micro powder 10a. Conversely, the peak on the side with larger particle size is referred to as the second peak (Peak2), and the particle group possessing this second peak is referred to as main powder 10b. The aforementioned small particles 11 are contained in micro powder 10a, and the large particles 12 are contained in main powder 10b.
[0054] like Figure 2 As shown, when the metallic magnetic powder 10 contains micro powder 10a and main powder 10b, the position of the first peak is preferably less than 1 μm. That is, the average value (arithmetic mean diameter) of the black ootheca diameter of micro powder 10a is preferably less than 1 μm, more preferably 0.2 μm or more and less than 1 μm.
[0055] On the other hand, the position of the second peak is preferably 5 μm or more and less than 40 μm. That is, the average value (arithmetic mean diameter) of the black ooder diameter of the main powder 10b is preferably 5 μm or more and less than 40 μm, more preferably 10 μm or more and less than 35 μm.
[0056] The particle size distribution and average value of the Black-Oud diameter of the metallic magnetic powder 10 can be calculated simply by analyzing the cross-section of the magnetic core 2 using an electron microscope or similar instrument. For example, an arbitrary cross-section of the magnetic core 2 can be divided into multiple consecutive fields of view for observation, and the Black-Oud diameter of each soft magnetic metal particle contained in each field of view can be measured. Preferably, the area of each field of view is set to be equivalent to 100 μm × 100 μm, and the number of observed fields of view is set to at least 100. Furthermore, it is preferable to measure the Black-Oud diameter of at least 1000 soft magnetic metal particles.
[0057] When the metallic magnetic powder 10 contains micro powder 10a and main powder 10b, any cross-section of the magnetic core 2 can be divided into multiple consecutive fields of view for observation, and the average diameter (average value of the black-wood diameter) of the micro powder 10a and the main powder 10b can be calculated. When calculating the average diameter of the micro powder 10a, it is preferable to set the area of each field of view to be equivalent to an area of 10 μm × 10 μm, and the number of observed fields of view to be at least 100. Furthermore, the number of micro powder constituent particles used to determine the black-wood diameter is preferably at least 1000. When calculating the average diameter of the main powder 10b, it is preferable to set the area of each field of view to be equivalent to an area of 100 μm × 100 μm, and the number of observed fields of view to be at least 100. Furthermore, the number of main powder constituent particles used to determine the black-wood diameter is preferably at least 1000.
[0058] It should be noted that the metallic magnetic powder 10 can also consist of three particle groups. In the case where the metallic magnetic powder 10 comprises three particle groups, Figure 2 In the particle size distribution shown, a third peak based on medium-diameter powder is preferably present between the first peak and the second peak. The average value of the black ooder diameter of the medium-diameter powder (i.e., the third peak) can be set, for example, to be greater than 2 μm and less than 5 μm.
[0059] Each particle constituting the metallic magnetic powder 10 is composed of a soft magnetic metal, and its composition is not particularly limited. For example, each soft magnetic metal particle of the metallic magnetic powder 10 can be pure iron, a crystalline alloy, a nanocrystalline alloy, or an amorphous alloy. Examples of crystalline soft magnetic alloys include Fe-Ni alloys, Fe-Si alloys, Fe-Si-Cr alloys, Fe-Si-Al alloys, Fe-Si-Al-Ni alloys, Fe-Ni-Si-Co alloys, Fe-Co alloys, Fe-Co-V alloys, Fe-Co-Si alloys, or Fe-Co-Si-Al alloys. Examples of soft magnetic alloys that are either nanocrystalline or amorphous include Fe-Si-B alloys, Fe-Si-BC alloys, Fe-Si-BC-Cr alloys, Fe-Nb-B alloys, Fe-Nb-BP alloys, Fe-Nb-B-Si alloys, Fe-Co-PC alloys, Fe-Co-B alloys, Fe-Co-B-Si alloys, Fe-Si-B-Nb-Cu alloys, Fe-Si-B-Nb-P alloys, and Fe-Co-BP-Si alloys.
[0060] Small particles 11 and large particles 12 can have the same compositional system or different compositional systems. For example... Figure 2 As shown, when the metallic magnetic powder 10 is composed of two particle groups, it is preferable that the micro powder 10a containing small particles 11 and the main powder 10b containing large particles 12 have different compositions. For example, from the viewpoint of reducing coercivity, the main powder 10b preferably has a nanocrystalline or amorphous alloy composition. On the other hand, the micro powder 10a is preferably a pure iron powder such as carbonyl iron powder, or a crystalline alloy powder such as Fe-Ni or Fe-Si.
[0061] The composition of the metallic magnetic powder 10 can be analyzed, for example, using an EDX (Energy Dispersive X-ray Analysis) device or EPMA (Electron Probe Microanalyzer) attached to an electron microscope. In cases where the micropowder 10a and the main powder 10b have different compositional systems, it is sometimes possible to identify the micropowder 10a and the main powder 10b by using surface analysis with an EDX device or EPMA.
[0062] Furthermore, detailed compositional analysis can also be performed using 3DAP (3D Atomic Probe) in EDX or EPMA devices. When using 3DAP, the composition of soft magnetic metal particles can be determined within the analyzed area, excluding the influence of resin components, surface oxidation, etc. This is because 3DAP can define a small region (e.g., a region of Φ20nm × 100nm) within the soft magnetic metal particles to determine the average composition.
[0063] Furthermore, the crystal structure of the metallic magnetic powder 10 can be analyzed using XRD, electron diffraction, etc. In this embodiment, amorphous refers to a degree of amorphization X of 85% or more, or where no crystallization-related points are identified in electron diffraction. The crystal structure of amorphous materials includes structures composed primarily of amorphous materials or structures composed of polycrystalline materials. In the case of a polycrystalline structure, the average crystal grain size of the crystals present in the amorphous material is preferably 0.1 nm or more and 10 nm or less. In addition, in this embodiment, "nanocrystalline" refers to a crystalline structure with a degree of amorphization X of less than 85% and an average crystal grain size of 100 nm or less (preferably 3 nm to 50 nm), and "crystalline material" refers to a crystalline structure with a degree of amorphization X of less than 85% and an average crystal grain size of more than 100 nm.
[0064] In the metallic magnetic powder 10, an insulating film is preferably formed to cover the surface of the particles. The insulating film can be formed separately on each of the soft magnetic metal particles constituting the metallic magnetic powder 10, and the metallic magnetic powder 10 may also include soft magnetic metal particles with and without an insulating film. For example... Figure 2 As shown, when the metallic magnetic powder 10 consists of two particle groups, it is particularly preferable to form an insulating film on the surface of the large particles 12 contained in the main powder 10b. An insulating film can also be formed on the surface of the small particles 11 contained in the micro powder 10a, in a manner that covers the particle surface.
[0065] The insulating film can be an oxide film containing the surface of particles (oxide film), or a film made of inorganic materials such as BN, SiO2, MgO, Al2O3, phosphates, silicates, borosilicates, bismuthates, or various glasses. The material of the insulating film is not particularly limited. Furthermore, the insulating film can also have a structure formed by stacking two or more films. The average thickness of the insulating film is preferably 1 nm to 200 nm, more preferably 50 nm or less.
[0066] Resin 20 functions as an insulating binder that fixes the metallic magnetic powder 10 in a predetermined dispersion state. Resin 20 preferably comprises a thermosetting resin such as epoxy resin.
[0067] Furthermore, the magnetic core 2 preferably contains a modifier for suppressing contact between the soft magnetic metal particles. Polymer materials such as polyethylene glycol (PEG), polypropylene glycol (PPG), and polycaprolactone (PCL) can be used as the modifier. A polymer having a polycaprolactone structure is particularly preferred. Examples of polymers having a polycaprolactone structure include carbamate raw materials such as polycaprolactone diol and polycaprolactone tetraol, or portions of polyesters. The content of the modifier relative to the total amount of the magnetic core 2 is preferably 0.025 wt% or more and 0.500 wt% or less. It is assumed that the modifier is adsorbed onto the surface of the soft magnetic metal particles by means of coating.
[0068] like Figure 1 As shown, small particles 11 and large particles 12 are dispersed in resin 20, with the small particles 11 filling the spaces between the large particles 12. In the magnetic core 2 of this embodiment, the interparticle distances of the small particles 11 and the interparticle distances between the small particles 11 and the large particles 12 are controlled in a manner that meets predetermined requirements. The dispersion state of the small particles 11 and the large particles 12 will be described in detail below.
[0069] First, based on Figure 3A and Figure 3B The analytical method for the dispersion state of small particles 11 is explained. Figure 3A In the cross-section of the magnetic core 2 shown, any small particle CP is selected from the small particles 11 present in the field of view (in... Figure 3A Small particles 11 are represented in gray. Then, the black-wood diameter of the small particle CP is measured, and half of its black-wood diameter is set as the radius r of the small particle CP. N Furthermore, the radius 3r is drawn from the center of gravity of the small particle CP. N The circle is defined as the region NC near the small particles CP.
[0070] Next, other small particles 11 existing in the vicinity NC of the small particle CP are identified. Here, these other small particles 11 are referred to as peripheral particles NP. Peripheral particles NP existing in the vicinity NC include small particles 11 whose entire circumference is contained within the vicinity NC, and small particles 11 whose portion exists within the vicinity NC (i.e., small particles 11 that extend from within the vicinity NC to the outside of the vicinity NC). For example, in... Figure 3A In the cross-sectional schematic diagram shown, there are 7 small particles 11, NP1 to NP7, in the NC region near the small particle CP.
[0071] After determining the nearby NC region and the surrounding particles NP (NP1~NP7), as follows Figure 3BAs shown, the edge distance between the small particle CP and the surrounding particle NP is measured. This edge distance is the distance from the outermost surface of the small particle CP to the outermost surface of the adjacent surrounding particle NP. For example, simply draw a straight line connecting the centroid of the small particle CP and the centroid of the surrounding particle NP2, and set the distance on this line from the outermost surface of the small particle CP to the outermost surface of the surrounding particle NP2 as the edge distance e2 between the small particle CP and the surrounding particle NP2. Furthermore, the outermost surface of the surrounding particle NP1 is in direct contact with the outermost surface of the small particle CP, and the edge distance e1 between the small particle CP and the surrounding particle NP1 is 0 μm.
[0072] It should be noted that, in Figure 3B In this context, the peripheral particles NP adjacent to the small particle CP refer to peripheral particles NP1 that are in direct contact with the small particle CP, and peripheral particles NP2 to NP6 that are adjacent to the small particle CP via resin 20. If other peripheral particles NP exist between particles, they are not considered "peripheral particles NP adjacent to the small particle CP". For example, ... Figure 3B As shown, there are other peripheral particles NP1 on the straight line connecting the centroid of peripheral particle NP7 and the centroid of small particle CP. Therefore, peripheral particle NP7 does not belong to "peripheral particles NP adjacent to small particle CP", and peripheral particle NP7 is set as an object outside the measurement of the distance between edges.
[0073] Following the above principles, measure the edge distances e1 to e6 between the small particle CP and each surrounding particle NP1 to NP6, and set the longest edge distance e1 to e6 as L1. That is, in the nearby region NC, set the edge distance between the small particle CP located at the center and the surrounding particle NP farthest from the center as L1. For example, in Figure 3B In the middle, the distance e6 between the edge of the small particle CP and the surrounding particle NP6 is equivalent to L1.
[0074] The above analysis was performed on at least 1000 small particles 11. That is, at least 1000 small particles 11 were selected as arbitrary small particle CPs, and L1 was measured in each small particle CP. The average value of L1 was set as L1av, and the average value (arithmetic mean diameter) of the Heude diameter of the small particles 11 was set as dav.
[0075] In the magnetic core 2 of this embodiment, the ratio of L1av to dav satisfies 5 ≤ ((L1av / dav) × 100) ≤ 70, preferably 15.5 ≤ ((L1av / dav) × 100) ≤ 69.5, and more preferably 16.5 ≤ ((L1av / dav) × 100) ≤ 50. L1av is preferably 0.030 μm or more and less than 0.450 μm, more preferably 0.100 μm or more and less than 0.400 μm.
[0076] In addition, such as Figure 3C As shown, the distance between the edges of small particles 11 and large particles 12 is measured. Specifically, in the cross-section of the magnetic core 2, any large particle 12 is selected from those present in the field of view. Then, small particles 11 that exist around and are adjacent to any large particle 12 are identified. Here, "adjacent" means directly in contact with any large particle 12, or adjacent to any large particle 12 via the resin 20. If other particles exist on the straight line connecting the centroids, they are not considered "small particles 11 adjacent to any large particle 12" and are excluded from the measurement of the distance between edges.
[0077] Measure the distance L2 between the edges of any large particle 12 and each small particle 11 adjacent to it. More specifically, draw a straight line connecting the centroid of any large particle 12 and the centroid of the small particles 11, and take the distance from the outermost surface of any large particle 12 to the outermost surface of the small particles 11 on this line as the distance L2 between the edges. When any large particle 12 is in direct contact with the adjacent small particles 11, L2 = 0 μm. Perform the above analysis on at least 100 large particles 12 to identify at least a total of 1000 small particles 11 adjacent to the large particle 12 being measured (i.e., set the number of n in L2 to at least 1000), and calculate the mean and standard deviation of L2. Set the mean of L2 as L2av, and the standard deviation of L2 as σ.
[0078] In the magnetic core 2 of this embodiment, L2av is 0.02 μm or more and 0.13 μm or less, preferably 0.03 μm or more and 0.12 μm or less, and more preferably 0.04 μm or more and 0.10 μm or less. Furthermore, the standard deviation σ of L2 is 0.25 μm or less, preferably 0.20 μm or less, and more preferably 0.10 μm or less.
[0079] As described above, by controlling the standard deviations σ of L1av / dav, L2av, and L2 within the specified ranges, it is possible to achieve both improved withstand voltage and enhanced DC superposition characteristics. In fact, Figure 4 The SEM image shown is an example of a magnetic core in which the standard deviations σ of L1av / dav, L2av, and L2 are controlled within specified ranges.
[0080] Furthermore, in the cross-section of the magnetic core 2, the area occupied by the small particles 11 is designated as S1, and the area occupied by the large particles 12 is designated as S2. In the magnetic core 2 of this embodiment, the ratio of S1 to S2 (S1 / S2) is preferably 0.2 or more and 0.5 or less. By satisfying 0.2 ≤ (S1 / S2) ≤ 0.5, the withstand voltage and DC superposition characteristics can be further improved. It should be noted that S1 / S2 can be measured using the same method as A1 / A2. In addition, when the metallic magnetic powder 10 contains micro powder 10a and main powder 10b, it is preferable to set the ratio of micro powder 10a to main powder 10b in a manner that satisfies the above-mentioned S1 / S2.
[0081] Furthermore, the average roundness of the large particles 12 in the cross-section of the magnetic core 2 is preferably 0.80 or higher, more preferably 0.90 or higher, and even more preferably 0.95 or higher. A higher average roundness of the large particles 12 further improves the withstand voltage and DC superposition characteristics. It should be noted that the roundness of each large particle 12 is defined as follows: S is the area of each large particle 12 in the cross-section of the magnetic core 2, L is the perimeter of each large particle 12, and 2(πS) is used. 1 / 2 / L represents the number of particles. The roundness of a perfect circle is 1. The closer the roundness is to 1, the higher the sphericity of the particle. It is preferable to measure and calculate the roundness of at least 100 large particles 12 to determine the average roundness.
[0082] It should be noted that there is no particular limitation on the average roundness of the small particles 11, but it is preferable that they have the same high average roundness as the large particles 12. Specifically, the average roundness of the small particles 11 is preferably 0.80 or higher.
[0083] Hereinafter, an example of a method for manufacturing the magnetic core 2 according to this embodiment will be described.
[0084] First, the raw material powder for manufacturing the metallic magnetic powder 10 is prepared. The method for manufacturing the raw material powder is not particularly limited. For example, it can be prepared by atomization methods such as water atomization or gas atomization. Alternatively, it can be prepared by synthesis methods such as CVD (chemical vapor deposition) using at least one of the following: evaporation, reduction, or thermal decomposition of a metal salt. Furthermore, the raw material powder can be prepared by electrolysis or carbonylation, or by pulverizing a starting alloy in a thin strip or plate. Among the above manufacturing methods, atomization is particularly preferred.
[0085] When small particles 11 and large particles 12 are formed using the same composition system, a raw material powder with a wide particle size distribution can be manufactured. This raw material powder is then graded to obtain a raw material powder containing small particles 11 and a raw material powder containing large particles 12. Alternatively, as the raw material powder for the metallic magnetic powder 10, it is preferable to separately manufacture a micronized raw material powder containing small particles 11 and a main powder raw material powder containing large particles 12. The arithmetic mean diameter of the micronized raw material powder is preferably less than 1 μm. Furthermore, the arithmetic mean diameter of the main powder raw material powder is preferably 5 μm or more and less than 40 μm, the D10 of the main powder raw material powder is preferably 2 μm or more, and the D90 of the main powder raw material powder is preferably 80 μm or less. The particle size of the micronized and main powder raw materials can be adjusted by the powder manufacturing conditions and various grading methods.
[0086] In addition, when an insulating film is formed on the surface of the metal magnetic powder 10 particles, the raw material powder can be subjected to film formation treatments such as heat treatment, phosphate treatment, mechanical alloying, silane coupling treatment, or hydrothermal synthesis.
[0087] The following describes a method for manufacturing the magnetic core 2 using micronized raw material powder and main powder raw material powder. First, the raw material powder of metallic magnetic powder and resin raw materials are mixed to obtain a resin composite. Typically, when two or more types of metallic magnetic powder are added to the magnetic core, the two or more raw material powders and resin raw materials are mixed and kneaded in a single step. In this embodiment, in order to control parameters such as L1av / dav, L2av, and σ within specified ranges, the kneading process is performed in two stages.
[0088] Specifically, in the first stage of primary mixing, fine-particle-size raw material powder, first resin raw material, and first solvent are mixed to obtain a primary resin composite. As the first resin raw material, a thermosetting resin such as epoxy resin can be used. As the first solvent, various organic solvents such as acetone, methyl ethyl ketone (MEK), and butyl carbitol acetate (BCA) can be used. In the second stage of secondary mixing, the primary resin composite, large-particle-size main powder raw material, second resin raw material, and second solvent are mixed to obtain a secondary resin composite. As described above, in the two-stage mixing process, it is preferable to first mix the fine-particle-size raw material powder, and then add the main powder raw material powder relative to the primary resin composite containing the fine-particle-size raw material powder, thus performing a secondary mixing.
[0089] In the two-stage mixing process, the magnetic powder concentration during the first mixing stage is set to be lower than that during the second mixing stage. Here, the magnetic powder concentration (wt%) during the first mixing stage is expressed as "(weight of the micronized raw material powder) / (total weight of the micronized raw material powder, the first resin raw material, and the first solvent) × 100". On the other hand, the magnetic powder concentration (wt%) during the second mixing stage is expressed as "(total weight of the main powder raw material powder and the micronized raw material powder in the first resin composite) / (total weight of the first resin composite, the main powder raw material powder, the second resin raw material, and the second solvent) × 100". The magnetic powder concentration during the first mixing stage is preferably set to 65wt% to 75wt%. The magnetic powder concentration during the second mixing stage is preferably 5wt% to 20wt% higher than that during the first mixing stage, and more preferably 70wt% to 90wt%.
[0090] The resin proportion in the primary resin composite is expressed as the weight ratio of the first resin raw material to 100 parts by weight of the micronized powder raw material, preferably 1 to 5 parts by weight. Furthermore, the proportion of the primary resin composite in the secondary mixing can be set such that S1 / S2 in the magnetic core 2 is within a desired range. Additionally, the resin proportion in the secondary resin composite is expressed as the weight ratio of the resin to 100 parts by weight of the magnetic powder (the total weight of the main powder raw material and the micronized powder raw material in the primary resin composite) (the total weight of the second resin raw material and the first resin raw material in the primary resin composite), preferably 1 to 5 parts by weight.
[0091] Furthermore, in the aforementioned mixing process, it is preferable to add the aforementioned modifier. The modifier can be added during the two mixing stages, but it is preferable to add it during both the first and second mixing stages. The amount of modifier added is preferably controlled such that the content of the modifier relative to the total amount of the magnetic core 2 is 0.025 wt% or more and 0.500 wt% or less. In addition to the modifier, preservatives, curing accelerators, etc., may also be added during the mixing process.
[0092] It should be noted that both primary and secondary mixing can be carried out using various mixing machines such as kneaders, planetary mixers, rotary mixers, or twin-screw extruders. For example, when using a rotary mixer, the resulting secondary resin composite can be dried at 60°C to 80°C for 1 to 24 hours to process it into particles with a particle size of approximately 50 μm to 350 μm.
[0093] Next, the obtained particles (secondary resin composite) are filled into a mold and compressed to obtain a molded body. The molding pressure can be set to, for example, 100 MPa to 800 MPa. It should be noted that the filling rate of the metallic magnetic powder in the magnetic core 2, and the A1 / A2 ratio, can be controlled based on the resin content, but can also be controlled by the molding pressure. The molded body is then held at 100°C to 200°C for 1 to 5 hours to cure the thermosetting resin. Through the above process, the magnetic core 2 is obtained.
[0094] The magnetic core 2 described in this embodiment can be applied to various magnetic components such as inductors, transformers, and choke coils. For example, Figure 5 The magnetic component 100 shown is an example of a magnetic component having a magnetic core 2.
[0095] exist Figure 5 In the magnetic component 100 shown, the base is composed of, for example... Figure 1 The magnetic core 2 shown is constructed. A coil 5 is embedded inside the magnetic core 2, which serves as the basic structure. The ends 5a and 5b of the coil 5 are led out to the end faces of the magnetic core 2. Furthermore, a pair of external electrodes 6 and 8 are formed on the end faces of the magnetic core 2, and these external electrodes 6 and 8 are electrically connected to the ends 5a and 5b of the coil 5, respectively. It should be noted that when the coil 5 is embedded inside the magnetic core 2, as in the case of the magnetic component 100, various parameters such as A1 / A2, S1 / S2, and edge distance are analyzed in the field of view not reflected by the coil 5.
[0096] Figure 5 The application of the magnetic component 100 shown is not particularly limited; for example, it is suitable for use as a power inductor in a power supply circuit. It should be noted that the magnetic component including the magnetic core 2 is not limited to... Figure 5 The method shown can also be used to form a magnetic component by winding a specified number of turns around the surface of a magnetic core 2 of a specified shape.
[0097] (Summary of Implementation Methods)
[0098] The magnetic core 2 associated with this embodiment comprises metallic magnetic powder 10 and resin 20, wherein the A1 / A2 ratio of the filling rate of the metallic magnetic powder 10 is 60% or more and 90% or less. Furthermore, the magnetic core 2 satisfies 5 ≤ ((L1av / dav)×100) ≤ 70, 0.02 μm ≤ L2av ≤ 0.13 μm, and σ ≤ 0.25 μm.
[0099] By giving the magnetic core 2 the above-mentioned characteristics, it is possible to improve voltage resistance and DC superposition characteristics while maintaining high relative permeability.
[0100] In addition, the average roundness of the large particles 12 contained in the magnetic core 2 is 0.80 or higher. By increasing the average roundness of the large particles 12, the withstand voltage and DC superposition characteristics can be further improved.
[0101] Furthermore, in the cross-section of the magnetic core 2, the ratio (S1 / S2) of the area S1 of the small particle 11 to the area S2 of the large particle 12 is 0.2 or more and 0.5 or less. By setting the ratio of the small particle 11 to the large particle 12 within the above range, the withstand voltage and DC superposition characteristics can be further improved.
[0102] The embodiments of this disclosure have been described above, but the present invention is not limited to the above embodiments, and various changes can be made within the scope of the present invention.
[0103] [Example]
[0104] The present invention will now be described in more detail based on specific embodiments. However, the present invention is not limited to the following embodiments.
[0105] (Experiment 1)
[0106] First, a micronized raw material powder containing small particles 11 and a main powder raw material powder containing large particles 12 are prepared. The micronized raw material powder is composed of crystalline pure iron powder, with an average particle size of 0.60 μm. On the other hand, the main powder raw material powder is composed of an amorphous Fe-Si-B alloy powder manufactured by high-pressure gas atomization, with an average particle size of 25 μm. It should be noted that the average particle size of the above-mentioned raw material powders is the arithmetic mean diameter of the equivalent circle diameter calculated based on the projected area of each particle, and is calculated using an image analysis device.
[0107] The raw material powder for micronized powder and the raw material powder for main powder are coated separately. An insulating film containing phosphate oxide is formed on the surface of the particles of the raw material powder for micronized powder, and the average thickness of the insulating film is 10 nm. In addition, an insulating film containing a composite oxide of borosilicate, Bi-based and phosphate-based compounds is formed on the surface of the particles of the raw material powder for main powder, and the average thickness of the insulating film is 20 nm.
[0108] In Experiment 1, the above-mentioned raw materials for micronized powder and raw materials for main powder were used to carry out the mixing process under the 12 conditions A to L shown in Table 1 to obtain the particles involved in Samples 1 to 12.
[0109] In condition A, the micronized powder, the main powder, the epoxy resin, and BCA (solvent) are mixed and kneaded in one step. On the other hand, in conditions B through L, kneading is performed in two stages. In each of these conditions B through L, in the first kneading stage, the raw material powder shown in Table 1, the epoxy resin (first resin), and BCA (first solvent) are kneaded; in the second kneading stage, the first resin composite, the raw material powder shown in Table 1, the epoxy resin (second resin), and BCA (second solvent) are kneaded. Furthermore, in each of conditions B through L, the magnetic powder concentration in the first and second kneading stages is set to the values shown in Table 1.
[0110] In all conditions A through L, the amount of raw material powder and primary resin composite added was set such that the weight ratio of micron powder to main powder was 2:8. Furthermore, in all conditions A through L, the amount of resin added was set such that the resin content in the particles was 2.5 parts by weight relative to 100 parts by weight of magnetic powder. It should be noted that no modifier was added in conditions A through L of Experiment 1. Additionally, in the above mixing process, a rotation / revolution mixer was used under all conditions, and the rotation speed, revolution speed, and stirring time were uniformly set for each condition.
[0111] In each sample of Experiment 1, the particles obtained in the above-mentioned mixing process were filled into a mold and pressurized to obtain a ring-shaped molded body. The molding pressure was controlled within a range of 40 ± 0.5 (unitless) for the relative permeability μi (relative permeability without a DC magnetic field (0 kA / m)) of the obtained magnetic core. Then, the molded body was heat-treated at 180°C for 60 minutes to cure the epoxy resin in the molded body, resulting in a ring-shaped magnetic core (outer diameter 11 mm, inner diameter 6.5 mm, thickness 1 mm).
[0112] In each sample of Experiment 1, the fabricated magnetic cores were evaluated as follows.
[0113] (Cross-sectional analysis of the magnetic core)
[0114] The cross-section of the magnetic core of each sample was observed using SEM. L1av / dav×100 (unitless), L2av (μm), and σ (μm) were measured using the method described in the embodiments. It should be noted that this cross-sectional analysis yielded the particle size distribution converted from the Black-Oud diameter of the metallic magnetic powder contained in the cross-section of the magnetic core. The results showed that in this experiment, the average diameter of the Black-Oud diameter of both the micro-powder and the main powder observed in the cross-section was approximately consistent with the average diameter of the raw material powder.
[0115] (Evaluation of withstand voltage characteristics)
[0116] In evaluating the withstand voltage characteristics, a cylindrical magnetic core was obtained using the same method as that used for manufacturing the toroidal magnetic core described above. In-Ga electrodes were formed at both ends of this magnetic core, and a voltage was applied to both ends of the magnetic core using a voltage boosting tester (THK-2011ADMPT). Then, the withstand voltage (unit: V / mm) was calculated based on the voltage value when a current of 1 mA flows and the length L of the magnetic core.
[0117] In Experiment 1, using the withstand voltage of sample 1 as a benchmark, the extent to which the withstand voltage of the other samples 2 to 12 improved relative to the benchmark was evaluated. That is, the withstand voltage of sample 1 was set as V. Ref The withstand voltage of the other samples 2 to 12 is set to V. N Calculate the voltage withstand improvement rate V N / V Ref Samples with a voltage withstand improvement rate of less than 1.1 times are designated as "F (Unacceptable)", samples with an improvement rate of more than 1.1 times but less than 1.3 times are designated as "G (Good)", samples with an improvement rate of more than 1.3 times but less than 1.5 times are designated as "VG (Even Better)", and samples with an improvement rate of more than 1.5 times are designated as "Ex (Exceptionally Good)".
[0118] (Evaluation of DC superposition characteristics)
[0119] In evaluating the DC superposition characteristics, firstly, polyurethane copper wire (UEW wire) is wound around the annular magnetic core of each sample. Then, a DC current is applied to this magnetic core in stages, starting from 0A. The inductance at the initial DC current of 0A is measured, and the current value Isat (in A) is measured when the inductance decreases by 10% after applying the DC current. A higher Isat value indicates better DC superposition characteristics.
[0120] In evaluating the DC superposition characteristics, the Isat of sample 1 is used as the benchmark to evaluate the extent to which the Isat of other samples 2 to 12 has improved relative to the benchmark. That is, the Isat of sample 1 is set as I. Ref Set Isat of the other samples 2 to 12 as I. N , calculate “I N -I Ref (Unit: A). This will satisfy (I) N -I Ref Samples with 0A ≤ 0A are designated as "F (unacceptable)" and samples satisfying 0A < (I N -I Ref Samples with an I<0.5A value are designated as "G (Good)" and samples that satisfy 0.5≤(I<0.5A) are designated as "G (Good)". N -I Ref Samples with an A value less than 1.0A are designated as "VG (better)" and will satisfy the condition 1.0A ≤ (I N-I Ref The sample was judged as "Ex (Excellent)".
[0121] The evaluation results of each sample in Experiment 1 are shown in Table 1.
[0122] [Table 1]
[0123]
[0124] As shown in Table 1, in Sample 1, which uses the existing method to mix micro powder and main powder in a single step, the small particles 11 are easily agglomerated, and ((L1av / dav)×100) is less than 5. On the other hand, in Samples 4 to 6 and Sample 11, which are samples that have undergone a two-stage mixing process, magnetic cores that satisfy 5≤((L1av / dav)×100)≤70, 0.02μm≤L2av≤0.13μm, and σ≤0.25μm are obtained. Moreover, in Samples 4 to 6 and Sample 11, where L1av / dav, L2av, and σ meet the specified requirements, both voltage withstand capability and DC superposition characteristics can be improved.
[0125] Based on the results of Experiment 1, it is known that in order to control L1av / dav, L2av, and σ within the specified range, a two-stage mixing process is preferred. Specifically, it is known that in the two-stage mixing process, fine-grained powder is preferably added in the first mixing stage, and the concentration of magnetic powder in each stage is controlled within an appropriate range, with the magnetic powder concentration in the first mixing stage set to be lower than that in the second mixing stage.
[0126] (Experiment 2)
[0127] In Experiment 2, the magnetic cores involved in samples A1 to A12, E1 to E15, and M1 to M22 were manufactured using the specified modifier.
[0128] Samples A1 to A12
[0129] Samples A1 to A12 are comparative examples, obtained by a single-stage mixing process as described in the literature. Specifically, the mixing conditions for sample A1 were the same as those in Experiment 1, namely, the micron powder, the main powder, the epoxy resin, and BCA were mixed and kneaded in one step. Samples A2 to A12 were also kneaded under the same conditions as sample A1, but with the addition of polypropylene glycol (PPG) as a modifier. The amount of modifier added in each sample was set as the content (wt%) of the modifier relative to the total amount of the magnetic core, as shown in Table 2.
[0130] In each of samples A1 to A12, crystalline pure iron powder was used as the raw material for micronized powder, with an average particle size of 0.59 μm. Additionally, amorphous Fe-Si-B alloy powder was used as the raw material for the main powder, with an average particle size of 25 μm. An insulating film with the same material and average thickness as in Experiment 1 was formed from these raw materials. Furthermore, the weight ratio of micronized powder to main powder was set uniformly in each of samples A1 to A12, satisfying "micronized powder: main powder = 3:7". The epoxy resin content was also uniformly set at 2.00 parts by weight per 100 parts by weight of magnetic powder in each of samples A1 to A12.
[0131] The magnetic cores involved in samples A1 to A12 were obtained under the same experimental conditions as in Experiment 1, except for the conditions mentioned above.
[0132] Samples E1 to E15
[0133] In samples E1 to E15, a two-stage mixing process was performed under the mixing conditions shown in Table 1 of Experiment 1, namely condition E. In samples E2 to E15, PPG was added as a modifier during the mixing process based on condition E. The modifier was added in both the first and second mixing stages, and the amount of modifier added was set to the values shown in Table 3, representing the content (wt%) of the modifier relative to the total amount of the magnetic core.
[0134] In each of the samples E1 to E15, the raw material for the micron powder was crystalline pure iron powder, and the raw material for the main powder was amorphous Fe-Si-B alloy powder. The weight ratio of micron powder to main powder was set to satisfy "micron powder: main powder = 3:7". For the raw material powders of each of the samples E1 to E15, an insulating film with the same material and average thickness as in Experiment 1 was also formed. Furthermore, the average particle size of the raw material powder for the micron powder, the average particle size of the raw material powder for the main powder, and the resin content of the particles after two mixing processes are shown in Table 3. Except for the above, the experimental conditions were the same as in Experiment 1, and the magnetic cores involved in samples E1 to E15 were obtained.
[0135] Sample M1 to Sample M11
[0136] Polycaprolactone (PCL) was added as a modifier in samples M1 to M11. In sample M1, the modifier was added during the first mixing step of condition A. In samples M2 to M11, the modifier was added during both the first and second mixing steps of condition E. The amount of modifier added in each sample was set as the content (wt%) of the modifier relative to the total amount of the magnetic core, as shown in Table 4.
[0137] In addition, in each of the samples M1 to M11, the raw material powder for the micron powder was crystalline pure iron powder with an average particle size of 0.59 μm, and the raw material powder for the main powder was amorphous Fe-Si-B alloy powder with an average particle size of 25 μm. An insulating film with the same material and average thickness as in Experiment 1 was formed in these raw material powders. Furthermore, the weight ratio of micron powder to main powder was set to satisfy "micron powder: main powder = 3:7", and the epoxy resin content in the particles was 2.00 parts by weight per 100 parts by weight of magnetic powder. Except for the above, the experimental conditions were the same as in Experiment 1, and the magnetic cores involved in samples M1 to M11 were obtained.
[0138] Samples M12 to M22
[0139] In samples M12 to M22, polyethylene glycol (PEG) was added as a modifier. In sample M12, the modifier was added during one stage of the mixing process in condition A. In samples M13 to M22, the modifier was added during both the first and second mixing stages in condition E. The amount of modifier added in each sample was set as the content (wt%) of the modifier relative to the total amount of the magnetic core, as shown in Table 5.
[0140] In addition, in each of the samples M12 to M22, the raw material powder for the micron powder was crystalline pure iron powder with an average particle size of 0.59 μm, and the raw material powder for the main powder was amorphous Fe-Si-B alloy powder with an average particle size of 25 μm. An insulating film with the same material and average thickness as in Experiment 1 was formed in these raw material powders. Furthermore, the weight ratio of micron powder to main powder was set to satisfy "micron powder: main powder = 3:7", and the content of epoxy resin contained in the particles was 2.00 parts by weight per 100 parts by weight of magnetic powder. Except for the above, the experimental conditions were the same as in Experiment 1, and the magnetic cores involved in samples M12 to M22 were obtained.
[0141] For each sample in Experiment 2, the cross-sectional analysis of the magnetic core, evaluation of voltage withstand characteristics, and evaluation of DC superposition characteristics were conducted using the same methods as in Experiment 1. In this experiment, the average diameter of the black ootheca diameter of the micro powder and main powder, measured by the cross-sectional analysis of the magnetic core, was approximately consistent with the average diameter of the raw material powder. Furthermore, in Experiment 2, the improvement rate of voltage withstand of other samples was evaluated using the voltage withstand of sample A1 as a benchmark. Regarding DC superposition characteristics, similarly, the improvement rate of DC superposition characteristics of other samples was evaluated using the Isat of sample A1 as a benchmark. The evaluation results for samples A1 to A12 are shown in Table 2, the evaluation results for samples E1 to E15 are shown in Table 3, the evaluation results for samples M1 to M11 are shown in Table 4, and the evaluation results for samples M12 to M22 are shown in Table 5.
[0142] [Table 2]
[0143]
[0144] [Table 3]
[0145]
[0146] [Table 4]
[0147]
[0148] [Table 5]
[0149]
[0150] As shown in Table 2, in the existing samples A1 to A12 that underwent one-stage mixing, even with the addition of a modifier, ((L1av / dav)×100) was less than 5, and no improvement in voltage withstand capability and DC superposition characteristics was achieved. On the other hand, as shown in Table 3, in the samples that underwent two-stage mixing, in samples E2 to E11 and samples E13 to E15 with the addition of a specified amount of modifier, magnetic cores satisfying 5≤((L1av / dav)×100)≤70, 0.02μm≤L2av≤0.13μm, and σ≤0.25μm were obtained. Moreover, in the samples where L1av / dav, L2av, and σ satisfied the above requirements, both voltage withstand capability and DC superposition characteristics were improved.
[0151] Furthermore, as shown in Tables 4 and 5, even with changes in the type of modifier, the same evaluation results as those for samples E1 to E15 can be obtained.
[0152] According to the results shown in Tables 2 to 5 of Experiment 2, L1av / dav, L2av, and σ can be controlled within the desired range by adjusting the modifier and its dosage. Furthermore, according to the results of Experiments 1 and 2 (Tables 1 to 5), it is evident that when all conditions are met—condition 1 "5 ≤ ((L1av / dav) × 100) ≤ 70", condition 2 "0.02 μm ≤ L2av ≤ 0.13 μm", and condition 3 "σ ≤ 0.25 μm"—both voltage withstand capability and DC superposition characteristics can be improved. It should be noted that the A1 / A2 ratios of the samples in Experiments 1 and 2 are within the range of 60% to 90%.
[0153] (Experiment 3)
[0154] In Experiment 3, the average particle size of the micron powder and the main powder were varied to manufacture magnetic cores for samples LS1 to LS70 and samples SS1 to SS16. For samples LS1 to LS70, the average particle size of the micron powder raw material was uniform, and the main powder raw material with the average particle sizes shown in Tables 6 to 15 was used. On the other hand, for samples SS1 to SS16, the average particle size of the main powder raw material was uniform, and the micron powder raw material with the average particle sizes shown in Table 16 was used.
[0155] The experimental conditions in Experiment 3, except for those mentioned above, were the same as in Experiment 2. Specifically, in each sample of Experiment 3, the raw material powder for the micron powder was crystalline pure iron powder with an insulating coating, and the raw material powder for the main powder was amorphous Fe-Si-B alloy powder with an insulating coating. Furthermore, the weight ratio of micron powder to main powder was set to satisfy "micron powder: main powder = 3:7", and the epoxy resin content in the particles was 2.00 parts by weight per 100 parts by weight of magnetic powder.
[0156] For each sample in Experiment 3, cross-sectional analysis, evaluation of withstand voltage characteristics, and evaluation of DC superposition characteristics of the magnetic core were performed using the same methods as in Experiment 1. In the cross-sectional observation of the magnetic core, the Black-Ude diameters of the micro-powder and main powder were measured. The results showed that the average particle size of the micro-powder and the average particle size of the main powder observed in the cross-section were consistent with the average particle sizes of the raw material powders shown in Tables 6 to 16. Furthermore, in Experiment 3, the mixing process was carried out under condition A, and the withstand voltage characteristics and DC superposition characteristics were evaluated using samples without modifiers (samples LS1, LS8, LS15, LS22, LS29, LS36, LS43, LS50, LS57, LS64, and A1) as a benchmark.
[0157] The evaluation results of samples LS1 to LS70 are shown in Tables 6 to 15, and the evaluation results of samples SS1 to SS16 are shown in Table 16.
[0158] [Table 6]
[0159]
[0160] [Table 7]
[0161]
[0162] [Table 8]
[0163]
[0164] [Table 9]
[0165]
[0166] [Table 10]
[0167]
[0168] [Table 11]
[0169]
[0170] [Table 12]
[0171]
[0172] [Table 13]
[0173]
[0174] [Table 14]
[0175]
[0176] [Table 15]
[0177]
[0178] [Table 16]
[0179]
[0180] The results shown in Tables 6 to 16 indicate that the average particle size of the micro powder and the main powder affects L1av / dav, L2av, and σ. That is, by appropriately adjusting the mixing conditions, the average particle size of the raw material powder, and the modifier, L1av / dav, L2av, and σ can be controlled within the desired range.
[0181] Furthermore, the results in Table 16 show that the smaller the average particle size of the micropowder, the better the voltage withstand characteristics and DC superposition characteristics (especially the voltage withstand characteristics). It is known that the average particle size of the micropowder is preferably less than 1 μm, and particularly preferably less than 0.5 μm.
[0182] (Experiment 4)
[0183] In Experiment 4, the amount of epoxy resin added was varied to manufacture magnetic cores for samples P1 to P7. The amount of epoxy resin added was set such that the A1 / A2 ratio of the magnetic core for each sample was the value shown in Table 17. The cross-sectional analysis, voltage withstand characteristics evaluation, and DC superposition characteristics evaluation of the magnetic cores were performed under the same experimental conditions as in Experiment 2, except as described above. In Experiment 4, the mixing process was carried out under condition A, and the voltage withstand characteristics and DC superposition characteristics were evaluated using the sample without modifier (sample A1 from Experiment 2) as a benchmark. The evaluation results of Experiment 4 are shown in Table 17.
[0184] [Table 17]
[0185]
[0186] As shown in Table 17, in samples P1 and P2 where A1 / A2 is less than 60%, L1av and L2av are larger than expected due to the low filling rate of magnetic powder. Furthermore, in sample P7 where A1 / A2 exceeds 90%, L1av and L2av are larger than expected due to the deterioration of the conformability of the magnetic core. In these samples P1, P2, and P7, no improvement in withstand voltage and DC superposition characteristics is achieved. On the other hand, in samples P3 to P6 where 60% ≤ A1 / A2 ≤ 90%, the withstand voltage and DC superposition characteristics are improved compared to the reference sample. Based on these results, it can be concluded that by setting the area ratio A1 / A2 of magnetic powder to a range of 60% or more and 90% or less, and by setting L1av / dav, L2av, and σ to a specified range, both withstand voltage and DC superposition characteristics can be improved.
[0187] (Experiment 5)
[0188] In Experiment 5, the roundness of large particles in the main powder was varied to manufacture the magnetic cores involved in samples R1 to R18. In each sample of Experiment 5, the roundness of the large particles was controlled by appropriately adjusting the melt temperature, melt injection pressure, gas pressure, and gas flow rate during powder fabrication based on gas atomization. The average roundness of each sample measured on the cross-section of the magnetic core is shown in Tables 18 and 19. It should be noted that, as shown in Table 18, the mixing process was carried out under existing condition A for samples R1 to R9; and as shown in Table 19, the mixing process was carried out under condition E (two-stage mixing conditions) for samples R10 to R18.
[0189] The experimental conditions other than those mentioned above were the same as in Experiment 2, and the cross-sectional analysis of the magnetic core, the evaluation of its withstand voltage characteristics, and the evaluation of its DC superposition characteristics were carried out. It should be noted that in Experiment 5, the mixing process was also carried out under condition A, and the withstand voltage characteristics and DC superposition characteristics were evaluated based on the sample without the addition of modifier (condition A of Experiment 1).
[0190] [Table 18]
[0191]
[0192] [Table 19]
[0193]
[0194] As shown in Table 18, in samples R1 to R9 where ((L1av / dav)×100) is less than 5, even adjusting the average roundness of the large particles does not improve the withstand voltage and DC superposition characteristics. On the other hand, as shown in Table 19, in samples R10 to R18 where L1av / dav, L2av, and σ are set within specified ranges, the higher the average roundness of the large particles, the more significantly the withstand voltage and DC superposition characteristics are improved. The results in Table 19 show that the average roundness of the large particles is preferably 0.80 or higher, and particularly preferably 0.95 or higher.
[0195] (Experiment 6)
[0196] In Experiment 6, the mixing ratio of main powder to micro powder was varied to manufacture the magnetic cores involved in samples S1 to S6. In each sample of Experiment 6, the amount of raw material powder for micro powder and main powder added during the mixing process was set with S1 / S2 as shown in Table 20. It should be noted that the S1 / S2 shown in Table 20 are measured values obtained through cross-sectional analysis of the magnetic cores.
[0197] In addition to the above, the experimental conditions were the same as in Experiment 2, including cross-sectional analysis of the magnetic core, evaluation of its withstand voltage characteristics, and evaluation of its DC superposition characteristics. It should be noted that in Experiment 6, the mixing process was also carried out under condition A, and the withstand voltage characteristics and DC superposition characteristics were evaluated using the sample without modifiers (condition A of Experiment 1) as the benchmark.
[0198] [Table 20]
[0199]
[0200] As shown in Table 20, in Experiment 6, the evaluation results of samples S2 to S5 were particularly good. This result indicates that the area ratio S1 / S2 of the small particles to the large particles is preferably 0.2 or higher and 0.5 or lower.
[0201] It should be noted that experiments were also conducted with variations in the composition of the metallic magnetic powder 10 (composition of small and large particles). The results showed that even with the variation in the composition of the metallic magnetic powder 10, the same trend was observed as in experiments 1 through 6 described above.
Claims
1. A magnetic core, wherein, The magnetic core comprises metallic magnetic powder and resin. Let A1 be the area of the metallic magnetic powder on the cross-section of the magnetic core, and let A2 be the total area of the metallic magnetic powder and the resin. The content of the metallic magnetic powder shall satisfy 60% ≤ (A1 / A2) ≤ 90%. The metallic magnetic powder contains small particles with a diameter of less than 1 μm and large particles with a diameter of more than 5 μm but less than 40 μm on the cross-section of the magnetic core. Let the radius of each of the small particles be r. N , Let the average value of the black oode diameter of the small particles be dav. On the cross-section of the magnetic core, from the center of gravity of each of the small particles to a radius of 3r N The area within the circumference is considered as the vicinity of each small particle. In the vicinity of each small particle, the distance between the edge of the small particle located at the center and the edge of the small particle farthest from the center is defined as L1. Let the average value of L1 be L1av. The ratio of L1av to dav satisfies 5 ≤ ((L1av / dav) × 100) ≤ 70. On the cross-section of the magnetic core, the distance between the edges of any large particle and any small particle adjacent to the large particle is defined as L2, the average value of L2 is defined as L2av, and the standard deviation of L2 is defined as σ. L2av is above 0.02μm and below 0.13μm. σ is below 0.25μm. Here, "adjacent" refers to a small particle that is in direct contact with any of the large particles, or is adjacent to any of the large particles via the resin, but is not adjacent to any of the large particles when there are other particles on the straight line connecting the centers of gravity. Such small particles are excluded from the measurement of the distance between edges.
2. The magnetic core according to claim 1, wherein, The average roundness of the large particles on the cross-section of the magnetic core is 0.8 or higher.
3. The magnetic core according to claim 1 or 2, wherein, On the cross-section of the magnetic core, let the area occupied by the small particles be S1. On the cross-section of the magnetic core, the area occupied by the large particle is S2. The ratio of S1 to S2 satisfies 0.2 ≤ (S1 / S2) ≤ 0.
5.
4. A magnetic component, wherein, It has a magnetic core as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Magnetic core for inductor, and inductor
JP2021176167A
Soft magnetic metal dust core and reactor having thereof
CN107658090A
Inductor
JP2021057470A